1992
DOI: 10.2307/2404486
|View full text |Cite
|
Sign up to set email alerts
|

Seed Bank Dynamics in a Mediterranean Grassland

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Applied Ecology. Summary 1. Changes in the seed bank, seedling eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
98
2
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 26 publications
16
98
2
2
Order By: Relevance
“…These germinability trends indicated high and low potential for producing persistent seed banks in these functional groups. These results are consistent with other studies from the Mediterranean region that showed that legumes and crucifers formed persistent seed banks, while grasses have little seed carry-over between years (Russi et al, 1992;Peco et al, 1998;Sternberg et al, 2003). Taxonomic similarities in seed morphology (e.g., seed coat impermeability in legumes) or physiological mechanisms of germination control may explain the homogeneity in dormancy trends within each group.…”
Section: Habitat Heterogeneity and Germination Strategiessupporting
confidence: 91%
“…These germinability trends indicated high and low potential for producing persistent seed banks in these functional groups. These results are consistent with other studies from the Mediterranean region that showed that legumes and crucifers formed persistent seed banks, while grasses have little seed carry-over between years (Russi et al, 1992;Peco et al, 1998;Sternberg et al, 2003). Taxonomic similarities in seed morphology (e.g., seed coat impermeability in legumes) or physiological mechanisms of germination control may explain the homogeneity in dormancy trends within each group.…”
Section: Habitat Heterogeneity and Germination Strategiessupporting
confidence: 91%
“…Research has shown that annuals are a major component of Mediterranean grasslands (Marcelo et al, 2003). The grazing of Mediterranean grasslands can have a large impact on vegetation (Montalvo et al, 1993;Seligman, 1996;Lavorel et al, 1999;Sternberg et al, 2000); however, the soil seed bank may buffer the impact of differences in inter-annual grazing (Russi et al, 1992;Ortega et al, 1997). It is generally assumed that Mediterranean annuals show adaptive responses to unpredictable environments by producing dormant seeds that persist during periods of limited resources (Shmida and Ellner, 1984;Thompson, 1992;Lavorel et al, 1993;Perevolotsky and Seligman, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of passive restoration in degraded ecosystems have found that passive restoration had positive [14][15][16][17], neutral [18], or even negative effects [19] on the species composition and density of the soil seed bank, as well as on the species composition, density, coverage, and mean height of vegetation. The different results mainly depended on the variety in seed production and emergence capacity, plant growth and dispersal, and the ratio of weeds to grass across the different grasslands [15].…”
Section: Introductionmentioning
confidence: 99%